Code Switching of Female & Male Lecturers In English Language Learning Of Fourth Year Students Of English Education Program At Universitas Negeri Padang - Nazhira Putri Daffiza; Nur Rosita (Journal of English Language Teaching, 2023)
This research was aimed to know the functions of code-switching in the classroom practised by female and male lecturers and investigated gender differences between female and male lecturers in the use of code-switching in the classroom. The researcher observed the classroom using audio recorder. Then, the data was analysed using mixed method research to measure the frequency of code-switching used by female and male lecturers in the classroom. The research subjects in this study were English education lecturers at Universitas Negeri Padang. Two female lecturers and two male lecturers.